1998
DOI: 10.2105/ajph.88.9.1319
|View full text |Cite
|
Sign up to set email alerts
|

Atopy in children and parental social class.

Abstract: OBJECTIVES: This analysis was conducted to determine whether atopic disorders were related to social class in a pediatric population of a former socialist country. METHODS: A cross-sectional study of 2471 schoolchildren was carried out in 1992 and 1993 in 3 towns in the former East Germany. Parents completed a standardized questionnaire regarding health events and lifestyle factors. In addition, skin-prick tests were performed and total serum immunoglobulin (IgE) was determined. RESULTS: Lifetime prevalence ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
0
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 29 publications
8
53
0
7
Order By: Relevance
“…The association between socioeconomic status and asthma in children is complex [18] and is likely to depend on asthma severity, poverty, many lifestyle factors and potentially also country of residence. While (probably severe) asthma prevalence is higher in children from less privileged families in inner cities, we previously found that asthma is more prevalent in the higher social classes in a large cohort of German children, which is consistent with other German studies [19]. The impact of atopy on asthma remains unclear.…”
Section: Discussionsupporting
confidence: 89%
“…The association between socioeconomic status and asthma in children is complex [18] and is likely to depend on asthma severity, poverty, many lifestyle factors and potentially also country of residence. While (probably severe) asthma prevalence is higher in children from less privileged families in inner cities, we previously found that asthma is more prevalent in the higher social classes in a large cohort of German children, which is consistent with other German studies [19]. The impact of atopy on asthma remains unclear.…”
Section: Discussionsupporting
confidence: 89%
“…This picture would seem to suggest that within communities, socioeconomic status is associated with asthma symptoms, but between communities with different lifestyles, asthma symptom prevalence is higher in affluent areas. This latter picture is consistent with the hygiene hypothesis and the picture of asthma prevalence in Europe [13,22,23].…”
Section: The Influence Of Socioeconomic Factorssupporting
confidence: 90%
“…The use of animal skin might be a lifestyle factor, which is difficult to assess more specifically. Since we observed more common use of animal skin in more educated families and since asthma is more common in better-educated families in Germany [41], the reported protective effect of sleeping on animal skin on asthma is not likely to be confounded by social factors.…”
Section: Discussionmentioning
confidence: 59%